Measuring Quality of Life in Carers of People With Dementia: Development and Psychometric Evaluation of Scales measuring the Impact of DEmentia on CARers (SIDECAR). (5th November 2019) - Horton, Mike C; Oyebode, Jan; Clare, Linda; Megson, Molly; Shearsmith, Leanne; Brayne, Carol; Kind, Paul; Hoare, Zoe; Al Janabi, Hareth; Hewison, Val; Tennant, Alan; Wright, Penny
Abstract: Background and Objectives: A 2008 European consensus on research outcome measures in dementia care concluded that measurement of carer quality of life (QoL) was limited. Three systematic reviews (2012, 2017, and 2018) of dementia carer outcome measures found existing instruments wanting. In 2017, recommendations were published for developing reliable measurement tools of carers' needs for research and clinical application. The aim of this study was to develop a new instrument to measure the QoL of dementia carers (family/friends). Methods: Items were generated directly from carers following an inductive needs-led approach. Carers ( n = 566) from 22 English and Welsh locations then completed the items and comparator measures at three time points. Rasch, factor, and psychometric (reliability, validity, responsiveness, and minimally important differences [MIDs]) analyses were undertaken. Results: Following factor analysis, the pool of 70 items was refined to three independent scales: primary SIDECAR-D (direct impact of caring upon carer QOL, 18 items), secondary SIDECAR-I (indirect impact, 10 items), and SIDECAR-S (support and information, 11 items). All three scales satisfy Rasch model assumptions. SIDECAR-D, I, S psychometrics: reliability (internal ≥ .70; test–retest ≥ .85); convergent validity (as hypothesized); responsiveness (effect sizes: D: moderate; I and S: small); MIDs (D = 9/100, I = 10/100, S = 11/100). Discussion and Implications: SIDECAR scales demonstrate robust measurement properties, meeting COSMIN quality standards for study design and psychometrics. SIDECAR provides a theoretically based needs-led QoL profile specifically for dementia carers. SIDECAR is free for use in public health, social care, and voluntary sector services, and not-for-profit organizations.